Garuḍajhepa : Sāvarakara gaurava grantha - Warhadpande, Vasant Krishna, 1927-; Joga, Vi. Sa., 1945-; Pāṇḍe, Ma (Vijaya Prakāśana, 1983)
Contributed articles on Vinayak Damodar Savarkar, 1883-1966, Indian freedom fighter.